Pharmacodynamics, Pharmacokinetics, and Antiviral Activity of BAY 81-8781, a Novel NF-κB Inhibiting Anti-influenza Drug - Droebner, Karoline; Haasbach, Emanuel; Dudek, Sabine E.; Scheuch, Gerhard; Nocker, Karlheinz; Canisius, Sebastian; Ehrhardt, Christina; von Degenfeld, Georges; Ludwig, Stephan; Planz, Oliver (Frontiers in Microbiology, 2017)
Influenza is a respiratory disease that causes annual epidemics. Antiviral treatment options targeting the virus exist, but their efficiency is limited and influenza virus strains easily develop resistance. Thus, new treatment strategies are urgently needed. In the present study we investigated the anti-influenza virus properties of D,L-lysine acetylsalicylate • glycine (BAY 81-8781; LASAG) that is approved as Aspirin i.v. for intravenous application. Instead of targeting the virus directly BAY 81-8781 inhibits the activation of the NF-B pathway, which is required for efficient influenza virus propagation. Using highly pathogenic avian influenza virus strains we could demonstrate that BAY 81-8781 was able to control influenza virus infection in vitro. In the mouse infection model, inhalation of BAY 81-8781 resulted in reduced lung virus titers and protection of mice from lethal infection. Pharmacological studies demonstrated that the oral route of administration was not suitable to reach the sufficient concentrations of BAY 81-8781 for a successful antiviral effect in the lung. BAY 81-8781 treatment of mice infected with influenza virus started as late as 48 h after infection was still effective in protecting 50% of the animals from death. In summary, the data represent a successful proof of the novel innovative antiviral concept of targeting a host cell signaling pathway that is required for viral propagation instead of viral structures.